Non-oriented electrical steel sheet and method for producing the same, and hot-rolled steel sheet

By optimizing the chemical composition and manufacturing process of the non-oriented electromagnetic steel plate, using the oxides of La, Ce, Zr, Mg and Ca elements, the problem of insufficient magnetic characteristics of the non-oriented electromagnetic steel plate in the prior art is solved, and stress removal is achieved Annealed high-performance steel plate.

CN116457477BActive Publication Date: 2024-12-13NIPPON STEEL CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080107501.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-27
Publication Date
2024-12-13
Estimated Expiration
2040-11-27

AI Technical Summary

Technical Problem

The prior art is difficult to manufacture non-oriented electromagnetic steel plates that fully and stably improve magnetic properties, especially in terms of crystal growth and iron loss during stress annealing.

Method used

By optimizing the chemical composition and manufacturing process of electromagnetic steel plates, the oxides containing specific proportions of La, Ce, Zr, Mg and Ca elements are controlled by controlling the number density and average interval of the oxides, combining hot rolling and cold rolling processes to ensure that After stress-relieving annealing, the crystal particle size reaches more than 50μm, reducing iron loss and improving magnetic flux density.

Benefits of technology

It is achieved at a low cost to provide a non-oriented electromagnetic steel plate with good growth properties of grains and excellent magnetic properties after stress annealing, and improves iron loss performance and magnetic flux density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004249375030000171
    Figure BDA0004249375030000171
  • Figure BDA0004249375030000181
    Figure BDA0004249375030000181
  • Figure BDA0004249375030000211
    Figure BDA0004249375030000211
Patent Text Reader

Abstract

A non-oriented electrical steel sheet, the chemical composition of which is expressed in mass %, comprises: C: 0.0050% or less, Si: 0.10-1.50%, Mn: 0.10-1.50%, sol.Al: 0.0050% or less, N: 0.0030% or less, S: 0.0040% or less, and O: 0.0050-0.0200%, and contains at least one element selected from the group consisting of La, Ce, Zr, Mg and Ca, with a total of 0.0005-0.0200%, and the remainder is Fe and impurities, and the number density N of appropriate oxides is 3.0×10 3 ~10×10 3 Pieces / cm 2 Moreover, the number density n of oxides including La satisfies n / N≥0.01.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a non-oriented electrical steel sheet and a method for manufacturing the same, and a hot-rolled steel sheet as a raw material of the non-oriented electrical steel sheet. Background Art

[0002] In recent years, with the increasing demand for energy-saving electrical appliances around the world, even non-oriented electromagnetic steel sheets used as core materials for rotating machines are required to have higher performance characteristics. Specifically, for products called high-efficiency models in the engines of electrical products, high-grade raw materials with increased Si and Al contents to increase inherent resistance and larger grain diameters are beginning to be used. In addition, even for general-purpose models, engines are beginning to be required to improve performance, but due to strict cost restrictions, it is actually difficult to change their materials to high-grade raw materials like high-efficiency models.

[0003] The steel sheets required for general-purpose machines have an Si content of less than 1.5%, and the iron loss is improved dramatically by growing crystal grains during stress relief annealing performed after punching of the motor core. In order to promote the growth of crystal grains during stress relief annealing, it is effective to reduce the amount of precipitates that are inevitably mixed into the steel, or to render such precipitates harmless.

[0004] For example, Patent Document 1 discloses a method for manufacturing an electric iron plate with excellent magnetic properties, which is characterized in that a hot-rolled plate is obtained by hot rolling a steel billet having C: ≤0.065%, Si: ≤2.0%, Al: ≤0.10%, O: ≤0.020%, B / N: 0.50~2.50%, and the remainder consisting of Fe and inevitable impurities, is formed into a final size by one cold rolling or two or more cold rollings including intermediate annealing, and then annealing is performed.

[0005] Patent document 2 discloses a non-oriented electromagnetic steel sheet with a low iron loss and an average grain size of 50 μm or more after magnetic annealing, which contains C: 0.015% or less, Si: 0.1-1.0%, sol.Al: 0.001-0.005%, Mn: 1.5% or less, S: 0.008% or less, N: 0.0050 or less, and TO: 0.02% or less, and is characterized in that the weight ratio of MnO to the total weight of three inclusions of SiO2, MnO, and Al2O3 in the steel is 15% or less.

[0006] Patent document 3 discloses an electromagnetic steel sheet having excellent magnetic properties, which contains, by weight, C: 0.01% or less, Si: 0.1% or more and 2.0% or less, Mn: 0.1% or more and 1.5% or less, and, depending on the deoxidation method of the steel, Al: 0.1% or less, or Zr: 0.05% or less, and the remainder is composed of iron and inevitable impurity elements, and is characterized in that among the oxides in the steel, oxides with a diameter of 0.5 μm or more and 5 μm or less are present per 1 cm 2 There are more than 1,000 and less than 50,000 of them.

[0007] Patent document 4 discloses a non-oriented electrical steel sheet, which contains, by mass%, C: 0.0050% or less, Si: 0.05-3.5%, Mn: 3.0% or less, Al: 3.0 or less, S: 0.008% or less, P: 0.15% or less, N: 0.0050% or less, Cu: 0.2 or less, and satisfies (S in Cu sulfide) / (S in steel)≤0.2, or (S in Cu sulfide) / (S in Mn sulfide)≤0.2, and further, the number density of Cu sulfides having a diameter of 0.03-0.20 μm in the steel sheet is 0.5 pieces / μm. 3 the following.

[0008] Patent document 5 discloses a non-oriented electrical steel sheet, characterized in that it contains, by mass%, Si: 1.5% or less, Mn: 0.4% or more and 1.5% or less, Sol.Al: 0.01% or more and 0.04% or less, Ti: 0.0015% or less, N: 0.0030% or less, S: 0.0010% or more and 0.0040% or less, B is 0.5 or more and 1.5 or less in terms of B / N, and the remainder is composed of Fe and inevitable impurities, among the sulfides containing Mn, 10% or more in terms of number ratio are complex precipitated with B precipitates, and the total distribution density of MnS, Cu2S and their complex sulfides is 3.0×10 5 Pieces / mm 2 Below, the distribution density of Ti precipitates with a diameter less than 0.1 μm is 1.0×10 3 Pieces / mm 2 the following.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 54-163720

[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 63-195217

[0013] Patent Document 3: Japanese Patent Application Laid-Open No. 3-104844

[0014] Patent Document 4: Japanese Patent Application Publication No. 2004-2954

[0015] Patent Document 5: International Patent Publication No. 2005 / 100627

[0016] Summary of the invention

[0017] Technical problem to be solved by the invention

[0018] However, when further improvement of magnetic properties is required, it is difficult to produce a non-oriented electrical steel sheet having sufficiently and stably improved magnetic properties by the above-mentioned conventional methods.

[0019] The present invention has been made in view of the above problems, and an object of the present invention is to provide a non-oriented electrical steel sheet having good grain growth during stress relief annealing, low iron loss after stress relief annealing, and high magnetic flux density after stress relief annealing, and a method for manufacturing the same, as well as a hot-rolled steel sheet that can be used as a raw material for the non-oriented electrical steel sheet.

[0020] Technical means for solving technical problems

[0021] The present invention has been made to solve the above-mentioned problems, and the gist of the present invention lies in the following non-oriented electrical steel sheet, a method for producing the same, and a hot-rolled steel sheet.

[0022] (1) A non-oriented electrical steel sheet, the chemical composition of which, in terms of mass%, comprises:

[0023] C: 0.0050% or less,

[0024] Si: 0.10~1.50%,

[0025] Mn: 0.10~1.50%,

[0026] sol.Al: 0.0050% or less,

[0027] N: 0.0030 or less,

[0028] S: 0.0040% or less, and

[0029] O: 0.0050~0.0200%,

[0030] Contains 0.0005 to 0.0200% in total of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca,

[0031] The rest: Fe and impurities,

[0032] The number density N of oxides containing 20 to 60% O and 20 to 60% Si in terms of mass % and having a diameter of 1.0 to 5.0 μm is 3.0×10 3 ~10×10 3 Pieces / cm 2 ,and,

[0033] The number density n of oxides of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca containing 1.0% or more in total, in terms of mass %, in the oxides satisfies the following formula (i).

[0034] n / N≥0.01……(i)

[0035] (2) The non-oriented electrical steel sheet according to (1) above, wherein the chemical composition, in place of a part of the Fe, contains, in terms of mass %,

[0036] Sn: 0.50% or less.

[0037] (3) The non-oriented electrical steel sheet according to (1) or (2) above,

[0038] The average interval between the oxides is 30 to 300 μm.

[0039] (4) The non-oriented electrical steel sheet according to any one of (1) to (3) above, wherein the average crystal grain size is 30 μm or less, and

[0040] The average grain size after stress relief annealing at 750° C. for 2 hours was 50 μm or more.

[0041] (5) A method for producing a non-oriented electrical steel sheet, which is the method for producing a non-oriented electrical steel sheet according to any one of (1) to (4), comprising:

[0042] Refining process, making molten steel,

[0043] a continuous casting step of continuously casting the molten steel to produce a slab having the chemical composition described in claim 1 or 2;

[0044] The hot rolling step is to heat the obtained slab and then perform hot rolling to produce a hot-rolled steel sheet.

[0045] A pickling step is performed on the hot-rolled steel sheet.

[0046] a cold rolling process, cold rolling the hot-rolled steel sheet after pickling to produce a cold-rolled steel sheet, and

[0047] The final annealing step is to perform final annealing on the cold-rolled steel sheet.

[0048] In the refining process,

[0049] The oxygen content of the molten steel before alloy addition is 0.010 to 0.050% by mass.

[0050] Then, the amount of Si added to the molten steel M1 and the Si content M2 in the slab are adjusted to satisfy the following formula (ii):

[0051] In the continuous casting process, a nozzle is used, wherein part or all of the inner wall of the nozzle in contact with the molten steel is made of a material containing, in total, 3 to 60% by mass of one or more oxides selected from the group consisting of La, Ce, Zr, Mg and Ca.

[0052] 0.90≤M2 / M1≤1.10……(ii)

[0053] (6) The method for producing a non-oriented electrical steel sheet according to (5) above, wherein in the refining step, the time from the completion of alloy addition to the start of the continuous casting step is set within a range of 30 to 180 minutes,

[0054] In the hot rolling step, the slab is immediately hot rolled after the temperature of the slab is maintained in a range of 1050° C. or higher and lower than 1150° C. for 15 to 240 minutes.

[0055] (7) The method for producing a non-oriented electrical steel sheet according to (5) or (6),

[0056] In the final annealing step, the temperature of the cold-rolled steel sheet is set to 800°C or higher and lower than 850°C.

[0057] (8) The hot-rolled steel sheet as a raw material of the non-oriented electrical steel sheet according to any one of (1) to (4) above, wherein the chemical composition comprises, in terms of mass %, the following:

[0058] C: 0.0050% or less,

[0059] Si: 0.10~1.50%,

[0060] Mn: 0.10~1.50%,

[0061] sol.Al: 0.0050% or less,

[0062] N: 0.0030 or less,

[0063] S: 0.0040% or less, and

[0064] O: 0.0050~0.0200%,

[0065] Contains 0.0005 to 0.0200% in total of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca,

[0066] The rest: Fe and impurities,

[0067] The number density N of oxides containing 20 to 60% O and 20 to 60% Si in terms of mass % and having a diameter of 1.0 to 5.0 μm is 3.0×10 3 ~10×10 3 Pieces / cm 2 ,and,

[0068] The number density n of oxides of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca containing 1.0% or more in total, in terms of mass %, in the oxides satisfies the following formula (i).

[0069] n / N≥0.01……(i)

[0070] (9) The hot-rolled steel sheet according to (8) above,

[0071] The chemical composition contains, in terms of mass%, Sn: 0.50% or less, replacing a part of the Fe.

[0072] (10) The hot-rolled steel sheet according to (8) or (9) above, characterized in that:

[0073] The average interval between the oxides is 30 to 300 μm.

[0074] Effects of the Invention

[0075] According to the present invention, a non-oriented electrical steel sheet having good grain growth during stress relief annealing and excellent magnetic properties can be stably provided at low cost. DETAILED DESCRIPTION

[0076] When non-oriented electrical steel sheets are used as materials for mechanical parts such as engine cores, they are first subjected to mechanical processing such as blanking, and then subjected to stress relief annealing, for example, at 750°C for 2 hours. During the stress relief annealing process, it is necessary to promote the growth of crystal grains in the steel sheet to reduce the iron loss of the steel sheet. Therefore, non-oriented electrical steel sheets must have a feature that can promote the growth of crystal grains during stress relief annealing.

[0077] As a factor in suppressing the growth of crystal grains during stress relief annealing, there are inclusions such as MnS that have a pinning effect. In the past, it was believed that reducing the amount of S, which is an element that generates inclusions, is effective in promoting the growth of crystal grains during stress relief annealing. However, S is an element that is inevitably mixed into steel, and the process of removing this element increases the manufacturing cost. In addition, attempts have been made to control the precipitation state of MnS by hot rolling conditions, but it cannot be said that the resulting improvement in characteristics is sufficient.

[0078] Here, the inventors found that when the oxides were finely precipitated during the manufacturing stage of the cast sheet as the material of the non-oriented electrical steel sheet, the iron loss of the steel sheet after stress relief annealing was improved. This is considered to be because MnS with a pinning effect was precipitated on the surface of the fine oxides and was rendered harmless. Furthermore, oxides containing 20 to 60% O and 20 to 60% Si and having a diameter of 1.0 to 5.0 μm (hereinafter also referred to as "appropriate oxides") have a particularly significant effect of rendering inclusions harmless, and the inventors found that the iron loss of the steel sheet can be improved by optimizing its number density.

[0079] However, the inventors of the present invention have further conducted repeated studies and found that, as described above, simply controlling the number density of appropriate oxides cannot stably achieve the effect of detoxifying MnS, and grain growth during stress relief annealing is suppressed at a certain rate.

[0080] Therefore, a method for stably rendering MnS harmless has been studied, and it has been conceived to fix S by using one or more elements selected from the group consisting of La, Ce, Zr, Mg, and Ca. However, when these elements are simply added, coarse inclusions containing these elements are generated, and the effect of rendering S harmless cannot be fully obtained.

[0081] After trying various methods of adding La and other elements, the inventors found that when using oxides containing these elements on the inner wall of the nozzle used in continuous casting and adding these elements to the molten steel by utilizing the dissolution of the nozzle, La and other elements do not form inclusions alone, but are contained in the above-mentioned appropriate oxides and are finely dispersed. Thus, the effect of detoxifying MnS can be stably obtained. In addition, it is not necessary to contain La and other elements in all the appropriate oxides, and the effect can be fully exerted as long as it is contained in a part of them.

[0082] The present invention has been accomplished based on the above findings. Hereinafter, each of the elements of the present invention will be described.

[0083] 1. Chemical composition

[0084] The chemical composition of the non-oriented electrical steel sheet and the hot-rolled steel sheet according to one embodiment of the present invention is described. The reasons for limiting each element are as follows. In the following description, "%" about the content means "% by mass".

[0085] C: 0.0050% or less

[0086] C deteriorates iron loss due to magnetic aging. Therefore, the C content is set to 0.0050% or less. Preferably, the C content is 0.0030% or less, or 0.0020% or less. In addition, since the non-oriented electromagnetic steel sheet involved in this embodiment does not require C, the lower limit of the C content is 0%. However, considering the cost of removing C mixed as an impurity, the lower limit of the C content may be set to 0.0001%, 0.0002%, or 0.0005%, for example.

[0087] Si: 0.10~1.50%

[0088] Si is an effective element for increasing electrical resistance. In addition, it is also an element necessary for forming the above-mentioned appropriate oxide. However, if Si is contained in an amount exceeding 1.50%, the hardness of the non-oriented electrical steel sheet increases, the magnetic flux density decreases, and the manufacturing cost increases. Therefore, the Si content is set to 0.10-1.50%. It is preferred that the Si content is 0.20% or more, 0.40% or more, or 0.80% or more. In addition, it is preferred that the Si content is less than 1.40%, less than 1.20%, or less than 1.00%.

[0089] Mn: 0.10~1.50%

[0090] Mn not only forms sulfides, but is also an effective element for increasing the resistance of non-oriented electrical steel sheets. In addition, it has the effect of preventing thermal cracks. However, when the Mn content is excessive, the phase transformation temperature drops excessively, and the grain size cannot be increased during stress relief annealing. Therefore, the Mn content is set to 0.10 to 1.50%. The Mn content is preferably 0.20% or more, 0.40% or more, or 0.80%. In addition, the Mn content is preferably 1.40% or less, 1.20% or less, or 1.00% or less.

[0091] sol.Al: 0.0050% or less

[0092] Al is an element generally used for deoxidation of steel. However, in the present invention, since Si is used for deoxidation, Al is not required in the non-oriented electrical steel sheet according to the present embodiment. In addition, if Al is contained excessively, a suitable oxide containing Si cannot be formed. Therefore, the sol.Al content is set to 0.0050% or less. The sol.Al content is preferably 0.0045% or less, or 0.0040% or less. However, considering the cost of removing Al mixed in as an impurity, the lower limit of the sol.Al content may be set to 0.0001%, 0.0002% or 0.0005%, for example.

[0093] N: 0.0030 or less

[0094] N is an element that may generate nitrides and has the risk of inhibiting grain growth. Therefore, the N content is preferably reduced as much as possible. However, it is industrially difficult to reduce the N content mixed into steel as an impurity to zero. In the present invention, as a harmless allowable amount, the N content is set to 0.0030% or less. In addition, the lower limit of the N content may also be 0.0001%, 0.0002%, or 0.0005%.

[0095] S: 0.0040% or less

[0096] S is an element that may generate sulfides and has the risk of inhibiting grain growth. Therefore, the S content is preferably reduced as much as possible. However, it is industrially difficult to reduce the S content mixed into steel as an impurity to zero. In the present invention, S is precipitated on the surface of the oxide to achieve S harmlessness. However, if the S content exceeds 0.0040%, the amount of sulfide precipitation itself increases, S harmlessness becomes difficult, and grain growth is hindered. Therefore, the S content is set to 0.0040% or less. In addition, the lower limit of the S content may also be 0.0001%, 0.0002%, or 0.0005%.

[0097] O: 0.0050~0.0200%

[0098] O is an element necessary for forming oxides. If the O content is too low, the required amount of oxides cannot be ensured. In addition, when the O content exceeds 0.200%, not only is the effect saturated, but also the number density of appropriate oxides is excessive, and these appropriate oxides agglomerate. Therefore, the O content is set to 0.0050-0.0200%. The O content is preferably 0.0055% or more, 0.0060% or more, or 0.0080% or more. In addition, the O content is preferably 0.0180% or less, 0.0150% or less, or 0.0100% or less.

[0099] One or more selected from the group consisting of La, Ce, Zr, Mg and Ca: 0.0005 to 0.0200% in total

[0100] By including La, Ce, Zr, Mg and Ca in the oxide mainly composed of O and Si, the effect of harmlessly degrading sulfides can be obtained more effectively and stably. In addition, when the content of these elements is excessively increased, the oxygen content in the steel is reduced, and coarse single oxides are generated, and the above-mentioned effect cannot be obtained. Therefore, the total content of one or more elements selected from La, Ce, Zr, Mg and Ca is set to 0.0005-0.0200%. The total content of these elements is preferably 0.0008% or more, 0.0010% or more, or 0.0020% or more, and preferably 0.0150% or less, 0.0100% or less, 0.0080% or less, 0.0070% or less, or 0.0060% or less. In addition, the effects of La, Ce, Zr, Mg and Ca are substantially the same in the non-oriented electrical steel sheet involved in this embodiment, so their content is specified by the total content.

[0101] Sn: 0.50% or less

[0102] In the present invention, Sn is not essential. However, Sn has the effect of inhibiting nitridation and oxidation of the steel sheet surface during stress relief annealing, and is an element effective in improving the magnetic flux density. In summary, an appropriate amount of Sn can be contained. However, even if more than 0.50% Sn is contained, the effect will be saturated, and the manufacturing cost will also increase. Therefore, the Sn content is set to 0.50% or less. It is preferred that the Sn content is less than 0.45%, less than 0.40%, or less than 0.30%. In addition, in the case of wanting to obtain the above-mentioned effect, it is preferred to set the Sn content to more than 0.01%, more than 0.02%, 0.03%, or 0.05%.

[0103] In the chemical composition of the non-oriented electrical steel sheet and the hot-rolled steel sheet according to the present embodiment, the remainder is Fe and impurities. Impurities refer to components mixed in industrially when steel is manufactured due to various factors such as raw materials such as ore or scrap, or the manufacturing process, and are components that can be allowed within the range that does not adversely affect the non-oriented electrical steel sheet according to the present embodiment.

[0104] 2. Oxide

[0105] The oxides contained in the non-oriented electrical steel sheet and the hot-rolled steel sheet according to the present embodiment are described. The non-oriented electrical steel sheet and the hot-rolled steel sheet according to the present embodiment contain 20 to 60% of O and 20 to 60% of Si by mass %, and contain appropriate oxides with a diameter of 1.0 to 5.0 μm. The number density N of the appropriate oxides is 3.0×10 3 ~10×10 3 Pieces / cm 2The number density of appropriate oxides is measured in the cross section of the non-oriented electrical steel sheet and the hot-rolled steel sheet, and is therefore defined as the number per unit area.

[0106] As described above, sulfides such as MnS that hinder the growth of crystal grains of non-oriented electrical steel sheets are rendered harmless by oxides. The mechanism is presumed as follows. When a slab as a material of a non-oriented electrical steel sheet is cast, oxides are first generated, and then MnS is precipitated. Here, MnS is precipitated on the surface of the oxides. If a large amount of oxides of a predetermined particle size are generated in the molten steel, the number of MnS precipitation sites increases, thereby achieving the detoxification of MnS.

[0107] The oxide effective for finely dispersing MnS is one whose chemical composition contains 20 to 60% O and 20 to 60% Si in mass%. It is considered that MnS tends to be difficult to precipitate on the surface of the oxide whose chemical composition is outside this range. Therefore, in the non-oriented electrical steel sheet and hot-rolled steel sheet according to the present embodiment, the number density of the substance having the above chemical composition in the oxide is specified.

[0108] In addition, from the perspective of promoting grain growth, among the oxides having the above chemical composition, oxides with a diameter of 1.0 to 5.0 μm are effective. Oxides with a diameter of less than 1.0 μm are not preferred because they themselves hinder grain growth. In addition, when the amount of coarse oxides with a diameter greater than 5.0 μm increases, the number density of oxides decreases. Therefore, in the non-oriented electrical steel sheet and hot-rolled steel sheet involved in this embodiment, the number density of oxides with a diameter of 1.0 to 5.0 μm is specified.

[0109] The number density N of suitable oxides that meet the above requirements is 3.0×10 3 ~10×10 3 Pieces / cm 2 When the number density N of the appropriate oxide is less than 3.0×10 3 / cm 2 When the number density N of the appropriate oxide exceeds 10×10 3 Pieces / cm 2 In other words, if the number density of the appropriate oxides is excessive, these appropriate oxides will aggregate and the fine dispersion effect of MnS cannot be obtained. The number density N of the appropriate oxides is 3.0×10 3 / cm 2 Above, 4.0×10 3 / cm 2 Above, or 5.0×10 3 / cm 2 The above are preferred.

[0110] In addition, the number density of oxides that do not satisfy the above requirements for chemical composition and particle size (e.g., oxides with a diameter of less than 1.0 μm and oxides with a diameter of more than 5.0 μm) is preferably reduced as much as possible. However, in the non-oriented electrical steel sheet and hot-rolled steel sheet having the above chemical composition, when the number density N of the appropriate oxides is controlled to 3.0×10 3 ~10×10 3 Pieces / cm 2 When the element that is the supply source of the oxide is consumed to generate the appropriate oxide. In this case, the generation of oxides that do not meet the above requirements, such as oxides with a diameter of less than 1.0 μm and oxides with a diameter of more than 5.0 μm, is necessarily suppressed. Therefore, it is not necessary to specify the number density of oxides that do not meet the above requirements.

[0111] Furthermore, in the non-oriented electrical steel sheet according to the present embodiment, among suitable oxides, the number density n of oxides containing, in mass %, 1.0% or more in total of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca satisfies the following formula (i).

[0112] n / N≥0.01……(i)

[0113] La, Ce, Zr, Mg and Ca (hereinafter referred to as "La, etc.") not only generate oxides but also generate sulfides, but the diameter of inclusions generated by these elements alone is as large as 5 μm or more. In contrast, oxides with O and Si as main components can exist in a relatively fine and dispersed state with a diameter of 1.0 to 5.0 μm as described above. Here, by compositely containing La, etc. in oxides with O and Si as main components, these elements can be dispersed at a high density that cannot be achieved in the case of oxides or sulfides of La, etc. In addition, it is believed that S, which is an impurity element, absorbs La, etc. and generates sulfides on the oxides, which can effectively and stably render S harmless.

[0114] The above effect can be obtained when the total concentration of La and the like in the appropriate oxide is 1.0 mass % or more. In addition, the number density n of the appropriate oxide containing La and the like (hereinafter also referred to as "La-containing oxide") is 1% or more of the number density N of the appropriate oxide. That is, the n / N value is 0.01 or more. The total concentration of La and the like in the appropriate oxide may also be 5.0 mass % or more, 10.0 mass % or more, or 20.0 mass % or more.

[0115] In addition, the number density N of appropriate oxides is measured by the following procedure. The oxides contained in the non-oriented electrical steel sheet or the hot-rolled steel sheet are observed by a scanning electron microscope (SEM). The observation magnification is set to 1000 times. The area of ​​the observation field is set to 25 mm. 2 The number of observation sites is set to 4 (i.e., the total area of ​​the observation field is 100 mm 2 Here, the chemical composition of each oxide is measured by an energy dispersive X-ray analyzer (EDS) attached to the SEM to determine whether each oxide contains 20 to 60% of O and 20 to 60% of Si in terms of mass %.

[0116] Then, the circular equivalent diameter of the oxide cross-sectional area is regarded as the diameter of the oxide, and the circular equivalent diameter of each oxide is judged to be 1.0 to 5.0 μm based on the image analysis of the electron microscope photograph taken using a transmission electron microscope (TEM). Based on these results, oxides containing 20 to 60% O and 20 to 60% Si by mass and a diameter of 1.0 to 5.0 μm are regarded as appropriate oxides, and the position of the appropriate oxide in each electron microscope photograph is determined. Then, the number density of the appropriate oxide is calculated by dividing the number of appropriate oxides contained in all electron microscope photographs by the sum of the field of view areas of all electron microscope photographs. In addition, there are sometimes cases where multiple oxides are observed to be aggregated, but in this case, the circular equivalent diameter is measured separately, and if the diameter is 1.0 to 5.0 μm, it is judged to be an appropriate oxide, and all of its numbers are counted.

[0117] In addition, the ratio (n / N) of the number density n of oxides containing La etc. to the number density N of appropriate oxides is calculated by the following procedure. The chemical composition of each appropriate oxide is measured by an energy dispersive X-ray analyzer (EDS) attached to the TEM to determine whether each appropriate oxide contains a total of 1.0 mass % or more of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca. Appropriate oxides containing a total of 1.0 mass % or more of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca are regarded as oxides containing La etc., and the position of oxides containing La etc. in each electron microscope photograph is determined. Then, by dividing the number of oxides containing La etc. contained in all electron microscope photographs by the number of all appropriate oxides, the ratio (n / N) of oxides containing La etc. to the number of appropriate oxides is calculated.

[0118] In addition, in order to prevent the appropriate oxides from agglomerating and to disperse them uniformly, it is preferred that the average interval between the appropriate oxides is 30 to 300 μm. By setting the average interval between the appropriate oxides to be 30 μm or more, the agglomeration distribution of the appropriate oxides can be suppressed, and the effect of detoxification of MnS can be more effectively exerted. In addition, in the agglomerated portion of the appropriate oxides, the deterioration of the mechanical and electromagnetic properties of the non-oriented electrical steel sheet can be suppressed. Therefore, it is preferred that the average interval between the appropriate oxides is 30 μm or more.

[0119] Similarly, if the average interval between the appropriate oxides is 300 μm or less, the appropriate oxides are in a properly dispersed state, so the precipitation position of MnS can be fully ensured. Therefore, it is preferred that the average interval between the appropriate oxides is 300 μm or less. It is more preferred that the average interval between the appropriate oxides is 35 μm or more, 40 μm or more, or 50 μm or more. In addition, it is more preferred that the average interval between the appropriate oxides is 280 μm or less, 250 μm or less, or 220 μm or less.

[0120] The average spacing of the appropriate oxides is obtained by the following method: based on the information of the particle size and position of the appropriate oxides in each electron microscope photograph determined in the above step, the distance between the appropriate oxides is measured and the average value is calculated. In addition, in the case where multiple oxides are observed to be agglomerated, since the appropriate oxides are stuck together, there is also a case where the distance is 0. However, in the present invention, in this case, the case where the distance is 0 is not used for the calculation of the average value. That is, even if the number density of the oxides is the same, the average spacing will become larger when partial agglomeration occurs.

[0121] 3. Crystalline particle size

[0122] The grain size of the non-oriented electromagnetic steel sheet involved in this embodiment is not particularly specified. As described above, when the non-oriented electromagnetic steel sheet is used after machining and stress relief annealing, the grain size changes according to the conditions of the stress relief annealing. Taking into account the above-mentioned actual use, as long as the grain growth in the stress relief annealing is good, it is not necessary to specify the grain size at the stage of the non-oriented electromagnetic steel sheet. However, if the average grain size is set to less than 30μm, the punching workability is improved. Therefore, the average grain size can also be set to less than 30μm. As a means of setting the average grain size to less than 30μm, known techniques can be appropriately used.

[0123] Generally speaking, non-oriented electrical steel sheets are provided for machining and stress relief annealing after leaving the factory. When the average grain size after the stress relief annealing is 50 μm or more, the iron loss characteristics are greatly improved. Since the non-oriented electrical steel sheet involved in this embodiment preferably controls the chemical composition and the state of the oxide, the average grain size after stress relief annealing at 750°C for 2 hours is 50 μm or more. In addition, in actual products, the stress relief annealing conditions are not limited to the above conditions. Considering the equipment constraints and the promotion of grain growth, the annealing temperature and time can also be appropriately changed.

[0124] The average grain size of the non-oriented electrical steel sheet can be obtained by the following method. The L section (a section parallel to the rolling direction) of the non-oriented electrical steel sheet is ground and etched, and then observed using an optical microscope. The observation magnification is set to 100 times, and the observation field area is set to 0.5 mm. 2 The number of observation sites was set to 3. By applying JIS G0551:2013 "Steel - Microscopic test method for grain size" to these optical microscope photographs, the average grain size of the non-oriented electrical steel sheet was determined.

[0125] 4. Manufacturing method

[0126] The method for producing a non-oriented electrical steel sheet according to the present embodiment includes a refining step, a continuous casting step, a hot rolling step, a pickling step, a cold rolling step, and a final annealing step. Among them, the refining step and the continuous casting step are particularly important for controlling oxides.

[0127] (a) Refining process

[0128] In the refining process, molten steel is produced. This process is a process of preparing the composition of the slab by adding alloying elements to the molten steel. After the addition of the specified alloy to the molten steel is completed, the amount of oxides generated gradually increases during the continuous casting process described below until the molten steel solidifies. Furthermore, oxides that float and mix into the slag are also generated. Therefore, in order to make the appropriate oxide number density 3.0×10 3 ~10×10 3 Pieces / cm 2 First, the oxygen content of the molten steel before alloy addition is adjusted to 0.010-0.050% by mass. In the case of insufficient oxygen content, the number density of the generated oxides is insufficient. In addition, in the case of excessive oxygen content, the number density of the oxides is excessively increased, and the oxides agglomerate.

[0129] Next, Si is added to the molten steel. Here, the amount of Si added to the molten steel M1 (mass %) and the Si content M2 (mass %) in the slab finally obtained in the subsequent continuous casting process satisfy the following formula (ii). Here, the amount of Si added to the molten steel M1 refers to the value obtained by dividing the total mass of Si added to the molten steel by the total mass of the molten steel (%). The Si content M2 of the slab refers to the Si content in the chemical composition of the slab, which is substantially the same as the Si content of the hot-rolled steel sheet and the non-oriented electromagnetic steel sheet obtained from the slab.

[0130] 0.90≤M2 / M1≤1.10……(ii)

[0131] When the Si content M2 of the slab is too small relative to the Si addition amount M1 to the molten steel and is less than 0.9 times of M1, a large amount of Si is mixed into the slag as SiO2 and discharged out of the molten steel, and Si deoxidation is excessively performed. Therefore, the number density of oxides in the slab cannot be made within the preferred range. In addition, when the Si content M2 of the slab is too large relative to the Si addition amount M1 to the molten steel and exceeds 1.10 times of M1, Si deoxidation does not progress, and the number of oxides increases excessively, and agglomeration of oxides occurs.

[0132] As described above, the Si content M2 in the molten steel is substantially the same as the Si content of the hot-rolled steel sheet and the non-oriented electrical steel sheet finally obtained. Therefore, the Si content M2 in the molten steel is set to 0.10 to 1.50%.

[0133] In addition, about the time from alloy addition to the end to the continuous casting process starting, considering the required time of making coarse oxide float from molten steel, it is preferably set as more than 30 minutes. In addition, if the time from alloy addition to the end to the continuous casting process starting is too long, then fine oxide can not remain in the molten steel, therefore from the viewpoint of guaranteeing the residual of this oxide, the time from alloy addition to the end to casting is preferably below 180 minutes. By adjusting the O amount and the Si addition before the alloy addition in this time range, the appropriate average interval of the above-mentioned regulation can be obtained.

[0134] (b) Continuous Casting Process

[0135] The molten steel produced in the refining process is continuously cast in the continuous casting process to produce a slab having the above chemical composition. This process is an important process for making La and the like contained in some appropriate oxides. When La and the like are added by methods such as the addition of mixed rare earths, a violent reaction occurs between these elements and the molten steel, resulting in a significant reduction in the oxygen content in the steel and the mixing of impurity elements in the slag into the molten steel. In addition, the generated oxide has a diameter exceeding 5 μm and is very coarse.

[0136] Therefore, in the manufacturing method according to the present embodiment, in the continuous casting process, a nozzle is used, wherein a part or the whole of the inner wall of the nozzle in contact with the molten steel is composed of a material containing 3 to 60% by mass of an oxide containing La or the like. La or the like is supplied to the steel by dissolving the inner wall of the nozzle in contact with the molten steel. When La or the like is contained in the steel by this method, there is no effect on oxygen and slag in the steel, and the oxide of the Si main body generated thereafter is composited with these elements, and the sulfide can be effectively rendered harmless.

[0137] (c) Hot rolling process

[0138] In the hot rolling process, the slab obtained in the continuous casting process is heated and then hot rolled to form a hot rolled steel sheet. Through this process, a hot rolled steel sheet according to an embodiment of the present invention is manufactured. In addition, the processes after the hot rolling process do not have a substantial effect on the chemical composition and the state of the oxides. Therefore, as described above, the chemical composition and the state of the oxides of the hot rolled steel sheet are the same as those of the non-oriented electromagnetic steel sheet according to the present embodiment.

[0139] By making the slab heating temperature before hot rolling less than 1150°C, the appropriate oxides can be uniformly dispersed and the average interval between the appropriate oxides can be adjusted to an appropriate range. Therefore, it is preferred that the slab heating temperature is less than 1150°C. In addition, from the viewpoint of ensuring rollability, it is preferred that the lower limit of the slab heating temperature before hot rolling is set to 1050°C. Furthermore, it is preferred that the slab be hot rolled immediately after being kept in a temperature range of 1050°C or more and less than 1150°C for 15 to 240 minutes.

[0140] In addition, although there is no particular limitation on the reduction ratio in the hot rolling process, 90% or more is preferred. In addition, although there is no particular limitation on the thickness of the obtained hot-rolled steel sheet, 1.0 to 4.0 mm is preferred, and 2.0 to 3.0 mm is more preferred.

[0141] (d) Pickling process

[0142] In the pickling step, the hot-rolled steel sheet obtained by the hot rolling step is pickled. The pickling conditions are not particularly limited as long as they are within the normal range of the production conditions of the non-oriented electrical steel sheet.

[0143] (e) Cold rolling process

[0144] In the cold rolling process, the hot rolled steel sheet after pickling is cold rolled to form a cold rolled steel sheet. The cold rolling conditions are not particularly limited as long as they are within the normal range of the manufacturing conditions of the non-oriented electrical steel sheet. For example, the reduction rate in the cold rolling process is preferably 50 to 95%, and more preferably 75 to 85%.

[0145] (f) Final annealing process

[0146] In the final annealing process, the cold-rolled steel sheet obtained by the cold rolling process is subjected to final annealing. In the final annealing process, if the maximum reaching temperature (temperature of the cold-rolled steel sheet) is above 850°C, the grain size becomes too large, and defects may occur in the punching process performed before the stress relief annealing. In order to avoid this, it is preferred that the maximum reaching temperature is less than 850°C. In addition, if the maximum reaching temperature is less than 800°C, the recrystallization is insufficient, and defects may occur in the punching process. In order to avoid this, it is preferred that the maximum reaching temperature is above 800°C. In addition, in order to avoid excessive grain size and defects in the punching process performed before the stress relief annealing, it is preferred to set the time for which the temperature of the cold-rolled steel sheet is above 800°C to less than 15 seconds.

[0147] Although the thickness of the non-oriented electrical steel sheet manufactured through the above steps is not particularly limited, it is preferably 0.1 to 1.0 mm, and more preferably 0.2 to 0.7 mm.

[0148] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0149] Example

[0150] The slabs were manufactured by performing a refining process and a continuous casting process under various conditions, and the obtained slabs were subjected to a hot rolling process, a pickling process, a cold rolling process, and a final annealing process in sequence to produce non-oriented electrical steel sheets. The chemical composition of the non-oriented electrical steel sheets is shown in Table 1, and the manufacturing conditions thereof are shown in Table 2. In addition, each steel sheet was manufactured 5 times under the same conditions. In addition, in all steel sheets, the temperature of the steel sheet in the final annealing process was 800°C or more, and the time was less than 15 seconds.

[0151] The contents of La, Ce, Zr, Mg, and Ca in the steel were adjusted only by dissolving the nozzle material in the continuous process except for Test No. 24. In addition, for Test No. 24, the composition was adjusted by adding alloy elements to the molten steel in the refining process.

[0152] [Table 1]

[0153] Table 1

[0154]

[0155] [Table 2]

[0156]

[0157] For the obtained non-oriented electrical steel sheet, the number density N of suitable oxides, the ratio (n / N) of the number density n of oxides containing La etc. to the number density N of suitable oxides, the average spacing between suitable oxides, and the average crystal grain size were measured by the following method. Then, the measured values ​​obtained from 5 steel sheets were averaged to obtain the respective measurement results.

[0158] The oxides contained in the non-oriented electrical steel sheet were observed by SEM at a magnification of 1000 times. The area of ​​the observation field was set to 25 mm 2 The number of observation sites is set to 4 (i.e., the total area of ​​the observation field is 100 mm 2 ) Here, the chemical composition of each oxide is measured by EDS attached to SEM to determine whether each oxide contains 20 to 60% of O and 20 to 60% of Si in terms of mass %.

[0159] Then, the circle equivalent diameter of the oxide cross-sectional area is regarded as the diameter of the oxide, and the circle equivalent diameter of each oxide is judged to be 1.0 to 5.0 μm based on the image analysis of the electron microscope photograph taken using TEM. Based on these results, oxides containing 20 to 60% O and 20 to 60% Si by mass and having a diameter of 1.0 to 5.0 μm are regarded as appropriate oxides, and the position of the appropriate oxide in each electron microscope photograph is determined. Then, the number density of the appropriate oxide is calculated by dividing the number of appropriate oxides contained in all electron microscope photographs by the sum of the field of view areas of all electron microscope photographs.

[0160] In addition, the chemical composition of each appropriate oxide is measured by EDS attached to TEM to determine whether each appropriate oxide contains a total of 1.0 mass% or more of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca. Appropriate oxides containing a total of 1.0 mass% or more of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca are regarded as La-containing oxides, and the position of La-containing oxides in each electron microscope photograph is determined. Then, by dividing the number of La-containing oxides contained in all electron microscope photographs by the number of all appropriate oxides, the ratio of La-containing oxides to the number of appropriate oxides (n / N) is calculated.

[0161] The average interval between the appropriate oxides is obtained by measuring the distances between the appropriate oxides based on the information on the particle sizes and positions of the appropriate oxides in the electron micrographs determined in the above steps, and calculating the average value thereof.

[0162] Furthermore, the L-section of the non-oriented electrical steel sheet was polished and etched, and then observed using an optical microscope. The observation magnification was set to 100 times, and the area of ​​the observation field was set to 0.5 mm2 The number of observation sites was set to 3. By applying JIS G 0551:2013 "Steel - Microscopic testing methods for grain size" to these optical microscope photographs, the average grain size of the non-oriented electrical steel sheet was determined.

[0163] Next, the obtained non-oriented electrical steel sheet was subjected to stress relief annealing at 750° C. for 2 hours. The following characteristics evaluation was performed on the non-oriented electrical steel sheet after the stress relief annealing.

[0164] (A) Iron loss after stress relief annealing

[0165] The iron loss (W15 / 50) of the steel sheet after stress relief annealing was measured in accordance with JIS C 2552:2014 "Non-oriented electrical steel strip". Non-oriented electrical steel sheets having a W15 / 50 of 5.0 W / kg or less after stress relief annealing were judged to have excellent iron loss characteristics after stress relief annealing.

[0166] (B) Magnetic flux density after stress relief annealing

[0167] The magnetic flux density (B 50 ). The B of the steel plate after stress relief annealing 50 The non-oriented electrical steel sheet having a strength of 1.70 T or more is judged to have excellent magnetic flux density after stress relief annealing.

[0168] (C) Grain growth during stress relief annealing

[0169] The average grain size of the steel sheet after stress relief annealing was measured by the same method as that of the non-oriented electrical steel sheet. A non-oriented electrical steel sheet having an average grain size of 50 μm or more after stress relief annealing was judged to have good grain growth during stress relief annealing.

[0170] (D) Punching processability

[0171] The blanking workability is evaluated using non-oriented electromagnetic steel sheets before stress relief annealing and after final annealing. Specifically, the steel sheet is blanked with a clearance of 7% to 12% of the sheet thickness. The burr height in the blanked portion is measured. Samples with a burr height of 30 μm or less are judged to have "good" blanking workability (symbol A). Samples with a burr height of more than 30 μm and less than 100 μm are judged to have "acceptable" blanking workability (symbol B). Samples with a burr height greater than 100 μm are judged to have "unacceptable" blanking workability (symbol C).

[0172] The above evaluation results are shown in Table 3.

[0173] [Table 3]

[0174]

[0175] As shown in Table 3, in Test Nos. 1 to 8, 22, 23, and 25 to 27 that meet the requirements of the present invention, excellent magnetic properties can be stably exhibited. In addition, in Test Nos. 9 to 16 whose chemical compositions do not meet the requirements of the present invention, at least one of the iron loss and magnetic properties deteriorates. In addition, in Test No. 17, since none of La, Ce, Zr, Mg, and Ca are contained, no oxide containing La or the like is formed. Therefore, although the average value of the iron loss becomes lower, the maximum value of the iron loss becomes higher because MnS cannot be stably rendered harmless.

[0176] In Test No. 18 to Test No. 21, the number density of appropriate oxides deviated from the specified range due to inappropriate manufacturing conditions, resulting in deterioration of iron loss. In Test No. 24, since the composition was adjusted by adding Mg and Ce to the molten steel in the refining process without utilizing the dissolution of the nozzle material, oxides containing La and the like were not sufficiently formed. As a result, although the average value of iron loss decreased, the maximum value of iron loss increased because MnS could not be stably rendered harmless.

[0177] Industrial Availability

[0178] According to the present invention, a non-oriented electrical steel sheet having good grain growth during stress relief annealing and excellent magnetic properties can be stably provided at low cost. Therefore, the present invention has extremely high industrial applicability.

Claims

1. A non-oriented electromagnetic steel sheet, The chemical composition is expressed in mass %, and contains: C: 0.0050% or less, Si: 0.10~1.50%, Mn: 0.10~1.50%, sol.Al: 0.0050% or less, N: 0.0030 or less, S: 0.0040% or less, and O:0.0050~0.0200%, and contains at least one element selected from the group consisting of La, Ce, Zr, Mg and Ca in an amount of 0.0005 to 0.0200% in total, The rest: Fe and impurities, The number density N of the oxides with a diameter of 1.0 to 5.0 μm is 3.0×10 3 ~10×10 3 Pieces / cm 2 ,and, The number density n of oxides of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca, which contain a total of 1.0% or more of the above elements, in terms of mass%, satisfies the following formula (i): n / N≥0.01……(i).

2. The non-oriented electrical steel sheet according to claim 1, The chemical composition contains, in terms of mass%, Sn: 0.50% or less, replacing a part of the Fe.

3. The non-oriented electrical steel sheet according to claim 1, The average interval between the oxides is 30 to 300 μm.

4. The non-oriented electrical steel sheet according to claim 2, The average interval between the oxides is 30 to 300 μm.

5. The non-oriented electrical steel sheet according to any one of claims 1 to 4, The average crystal grain size is 30 μm or less, and The average grain size after stress relief annealing at 750° C. for 2 hours was 50 μm or more.

6. A method for manufacturing a non-oriented electrical steel sheet, the method comprising: Refining process to produce molten steel; A continuous casting step, continuously casting the molten steel to produce a slab having the chemical composition of claim 1 or claim 2; A hot rolling step, heating the obtained slab and then hot rolling it to produce a hot-rolled steel sheet; A pickling step of pickling the hot-rolled steel plate; A cold rolling process is to cold roll the hot-rolled steel sheet after pickling to produce a cold-rolled steel sheet; as well as, The final annealing step is to perform final annealing on the cold-rolled steel sheet. In the refining process, The oxygen content of the molten steel before alloy addition is set to 0.010 to 0.050% by mass. Then, the amount of Si added to the molten steel M1 and the Si content M2 in the slab are adjusted to satisfy the following formula (ii): 0.90≤M2 / M1≤1.10……(ii) In the continuous casting process, a nozzle is used, wherein part or all of the inner wall of the nozzle in contact with the molten steel is made of a material containing, in total, 3 to 60% by mass of one or more oxides selected from the group consisting of La, Ce, Zr, Mg and Ca.

7. The method for producing a non-oriented electrical steel sheet according to claim 6, In the refining step, the time from the completion of alloy addition to the start of the continuous casting step is set within a range of 30 to 180 minutes. In the hot rolling step, the slab is immediately hot rolled after the temperature of the slab is maintained in a range of 1050° C. or higher and lower than 1150° C. for 15 to 240 minutes.

8. The method for producing a non-oriented electrical steel sheet according to claim 6 or claim 7, In the final annealing step, the temperature of the cold-rolled steel sheet is set to 800°C or higher and lower than 850°C.

9. A hot-rolled steel sheet, which is a raw material of the non-oriented electrical steel sheet according to any one of claims 1 to 5, The chemical composition is expressed in mass %, and contains: C: 0.0050% or less, Si: 0.10~1.50%, Mn: 0.10~1.50%, sol.Al: 0.0050% or less, N: 0.0030 or less, S: 0.0040% or less, and O:0.0050~0.0200%, Contains 0.0005 to 0.0200% in total of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca, The rest: Fe and impurities, The number density N of oxides containing 20 to 60% O and 20 to 60% Si in terms of mass % and having a diameter of 1.0 to 5.0 μm is 3.0×10 3 ~10×10 3 Pieces / cm 2 ,and, The number density n of oxides of one or more elements selected from the group consisting of La, Ce, Zr, Mg and Ca, which contain a total of 1.0% or more of the above elements, in terms of mass%, satisfies the following formula (i): n / N≥0.01……(i).

10. The hot rolled steel sheet according to claim 9, The chemical composition contains, in terms of mass%, Sn: 0.50% or less, replacing a part of the Fe.

11. The hot rolled steel sheet according to claim 9 or claim 10, The average interval between the oxides is 30 to 300 μm.